Enhancing New Student Enrollment Using an Integrated SWOT-QSPM Approach: A Case Study of XYZ University - Hisbulloh Ahlis Munawi; Indung Sudarso (Jurnal IPTEK, 2025)
Competition in the service industry, especially higher education, is becoming increasingly intense. This tight competition also affects University XYZ, resulting in a declining number of new students. The purpose of this study is to identify weaknesses, strengths, opportunities, and threats through a SWOT analysis, and to evaluate strategies using QSPM. The SWOT analysis results indicate that the main strategy involves utilizing reputation, diverse study programs, experienced lecturers, and high-achieving students to seize opportunities such as the increasing interest in pursuing higher education. The QSPM analysis shows that the SO strategy has a TAS value of 6.43, the ST strategy has a TAS value of 5.99, the WO strategy has a TAS value of 5.45, and the WT strategy has a TAS value of 5.21. The integration of both analyses results in implementable strategies for increasing new student enrollment, ensuring that the strategies can be effectively applied.